POLA PRODUKSI BIOLISTRIK KONSORSIUM BAKTERI TERMOFILIK SUMBER AIR PANAS SAPAN SUNGAI ARO - Irdawati; Annisa Fitri, Siti (Jurnal Biogenerasi, 2025)
This study aims to investigate the bioelectricity production pattern of a thermophilic bacterial consortium from Sapan Sungai Aro. Thermophilic bacteria, which can survive at high temperatures, have the potential to generate electricity through their metabolic activity. In this study, the thermophilic bacterial consortium was isolated from Sapan Sungai Aro and tested for bioelectricity production at a 5% concentration with various consortium ratios (1:2, 2:1, 1:3, 3:1). The data show that the stationary phase at the 20th hour produced the highest voltage, which was 0.764 V, at the 3:1 ratio. These results indicate that the optimal composition of the bacterial consortium influences the efficiency of bioelectricity production. Moreover, this study also reveals that both the exponential and stationary phases play important roles in electricity generation, with the stationary phase providing the most ideal metabolic conditions